GEOWISATA DAN WISATA EDUKASI: MERANCANG PAKET WISATA UNTUK KAWASAN RAWAN BENCANA - Wulung, Shandra Rama Panji; Andari, Rini; Kikania, Audy Putri; Abdilah, Muhammad Anthesa (Program Studi Pariwisata, UPN Veteran Jawa Timur, 2024)
The government is currently focused on creating sustainable tourism destinations in disaster areas, with special attention given to developing geotourism as a form of educational tourism. This research aims to design educational tour packages with a geotourism theme specifically for disaster-prone areas. The study was conducted in the Tangkubanparahu Volcano disaster-prone area of North Bandung, using a combination of observations, interviews, and library documents. The data obtained was analyzed through descriptive and map analysis. The results of the research showed that geotourism has great potential as a theme for educational tourism packages in the Tangkubanparahu Volcano disaster-prone area. The 10 km route includes natural, cultural, and man-made tourist attractions which are supported by the availability of tour guides